#### Answer

$\color{blue}{y=\frac{2}{3}(x-3)}$

#### Work Step by Step

RECALL:
(1) The point-slope form of a line's equation is $y-y_1=m(x-x_1)$ where $m$=slope and $(x_1, y_1)$ is a point on the line.
(2) The slope $m$ of a line that contains the points $(x_1, y_2)$ and $(x_2, y_2)$ is given by the formula $m=\dfrac{y_2-y_1}{x_2-x_1}$..
Solve for the slope using the formula in (2) above to obtain:
$m=\dfrac{-2-0}{0-3}
\\m=\dfrac{-2}{-3}
\\m=\dfrac{2}{3}$
With a slope of $\frac{2}{3}$, either of the two given points can be used to write the point-slope form of the line's equation.
Therefore, using the point $(3, 0)$ gives:
$y-0 = \frac{2}{3}(x-3)
\\\color{blue}{y=\frac{2}{3}(x-3)}$